Pengaruh Penambahan Tepung Kulit Singkong Pada Pembuatan Mi Basah Terhadap Cita Rasa - Fuadatul Luthfi; Adib Suyanto; Hary Haryono (Sanitasi: Jurnal Kesehatan Lingkungan, 2011)
In order to fulfill human needs, food production usually generates wastes as the byproduct. Cassava is one example of mass consumption food which yield waste from its peels. Since cassava peel has high carbohydrate content, to minimize the negative impacts of the waste, it can recycle into flour and be utilized as one of food ingredients wet noodle making. The purpose of this research was to know the color, smell, taste and texture produced by wet noodle which were consisted of 0%, 20%, 40%, 60% and 80% flour skin formulation, and threfore the best formulation can be identified. This study was an experiment with static group comparison design. As the panelist, five housewives were appointed to examine the noodles variation, and their cum-mulative scores were subsequently statistically analyzed. Results of the study showed that the p-value obtained from one way anova test was 0,001 which means there are differences across formulation variation, and the most accept-able cassava peel formulation was 20%.